Integrating mental health into climate change education to inspire climate action while safeguarding mental health - Newberry Le Vay, Jessica; Cunningham, Alex; Soul, Laura; Dave, Heena; Hoath, Leigh; Lawrance, Emma L. (Frontiers in Psychology, 2024)
Climate change is the greatest threat humanity faces, and puts at risk the mental health and wellbeing of children and young people. Climate change education must equip children and young people with the knowledge, skills and resilience to live in an uncertain future, sustainably take relevant climate action and work in climate careers. As attention on climate change education grows, this is a critical moment for the mental health community to ensure mental health and wellbeing considerations are embedded. Critically, appropriate integration of mental health can enable these very necessary goals of equipping children and young people to live and work in a future where climate change looms large. This paper explores why promoting good mental health and wellbeing and building psychological resilience can help achieve climate change education outcomes, and why not doing so risks harming children and young people’s mental health. It also explores how integrating discussions about emotions, mental health, and coping strategies within climate change education can be a route into wider discussions about mental health, to support children and young people in the context of rising mental health needs. Learning from an existing approach to promoting good mental health and wellbeing in schools (the ‘whole school approach’) provides the opportunity to explore one avenue through which such an integrated approach could be implemented in practice. Identifying appropriate mechanisms to integrate mental health into climate change education will require co-design and research with educators and young people, and addressing systemic barriers facing the schools sector.